The Effect of Working Capital and Financial Management on Sanrico Store MSME Income in Mojokerto Regency - Veby Shafira; Nersiwad; Rini Armin (International Journal of Management and Business Economics, 2023)
Micro, Small and Medium Enterprises (MSMEs) are productive businesses that are generally managed individually or by business entities and MSMEs themselves, including business fields that have a positive contribution in advancing the national economy. However, it is not uncommon to find problems in running MSMEs, such as in terms of working capital which will later be used to finance business operations and financial management which is still not properly recorded so that it can hinder the progress of these business activities. This study aims to determine the significant effect of working capital and financial management on the income of UMKM Sanrico Store. The type of research used is quantitative research with a descriptive approach. Data collection techniques used are interviews, observation, documentation. The method used in this research is Multiple Linear Regression Analysis, Classical Assumption Test, and Hypothesis Test using the SPSS program. Based on data management where the results of the T test in this study indicate that working capital has a positive and significant effect on income, and financial management also has a positive and significant effect on income. The simultaneous results with the F test in this study indicate that working capital and financial management simultaneously have a positive and significant effect on income. The value of R Square (R2) is 0.958 which indicates that 95.8% of working capital and financial management have an effect on income.